Preliminary investigation of the contribution of fast-ice algae to the spring phytoplankton bloom in Ellis Fjord, eastern Antarctica - Andrew McMinn (1996)
Algae released from fast-ice in Ellis Fjord, eastern Antarctica, made little contribution to subsequent phytoplankton growth. Dominant taxa in the interior ice community included Nitzschia cylindrus (Grun) Hasle, Navicula glaciei V.H. and a dinoflagellate cyst. Diatom mortality within the ice was high. The algal contribution to the phytoplankton from the fast ice was estimated by calculating the difference between algal biomass in ice cores taken on 14 November with those taken on 18 December 1992. The biomass of sedimenting phytoplankton was estimated using sediment traps; weekly cell counts of water were used to monitor net phytoplankton growth. The low contribution from the fast-ice of Ellis Fjord to the phytoplankton is similar to results from other Antarctic fast-ice communities but is not necessarily reflective of processes occurring within either Antarctic or Arctic pack ice communities. An algal mat growing on the base of the fast-ice had a carbon standing crop of between 0.231 gCm-2 and 0.022 gCm-2. Much of this was delivered to the water column as the ice melted while the remainder was exported.